Linking Theory and Practice of Digital Libraries 26th International Conference on Theory and Practice of Digital Libraries, TPDL 2022, Padua, Italy, September 20-23, 2022, Proceedings - Silvello, Gianmaria; Corcho, Oscar; Manghi, Paolo; Di Nunzio, Giorgio Maria; Golub, Koraljka; Ferro, Nicola; Poggi, Antonella (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the proceedings of the 26th International Conference on Theory and Practice of Digital Libraries, TPDL 2022, which took place in Padua, Italy, in September 2022. The 18 full papers, 27 short papers and 15 accelerating innovation papers included in these proceedings were carefully reviewed and selected from 107 submissions. They focus on digital libraries and associated technical, practical, and social issues. .
Keynote Talks -- Should we preserve the worlds software history, and can we? -- Full Papers -- Analyzing the Web: Are Top Websites Lists a Good Choice for Research? -- RDFtex: Knowledge Exchange between LATEX-based Research Publications and Scientific Knowledge Graphs -- Enriching the Greek National Cultural Aggregator with Key Figures in Greek History and Culture: Challenges, Methodology, Tools and Outputs -- Figure and Figure Caption Extraction for Mixed Raster and Vector PDFs: Digitization of Astronomical Literature with OCR Features -- FAIROs: Towards FAIR assessment in Research Objects -- Searching Wartime Photograph Archive for Serious Leisure Purposes -- Implementation and evaluation of a multilingual search pilot in the Europeana digital library -- DETEXA: Declarative Extensible Text Exploration and Analysis -- The way we cite: common metadata used across disciplines for defining bibliographic references -- Event Notifications in Value-Adding Networks -- A Chromium-based Memento-aware Web Browser -- Analysis of the deletions of DOIs What factors undermine their persistence and to what extent? -- Analysing User Involvement in Open Government Data Initiatives -- The Rise of GitHub in Scholarly Publications -- Whois? Deep Author Name Disambiguation using Bibliographic Data -- Investigations on Meta Review Generation From Peer Review Texts Leveraging Relevant Sub-tasks in the Peer Review Pipeline -- Improving Accessibility to Arabic ETDs using Automatic Classification -- Short Papers -- Robots Still Outnumber Humans in Web Archives, But Less Than Before -- Cui Bono? Cumulative Advantage in Open Access Publishing -- Overview visualizations for large digitized correspondence collections : a design study -- Developing the EOSC-Pillar RDM Training and Support Catalogue -- Automatic Generation of Coherent Image Galleries in Virtual Reality -- Extracting funder information from scientific papers - experiences with question answering -- CDX Summary: Web Archival Collection Insights -- \Knock knock! Whos there?" A study on scholarly repositories availability -- Exploring research fields through institutional contributions to academic journals -- Implementation Issues for a Highly Structured Research Report -- MINE Workspace as a Service for Text Analysis -- Conducting the Opera: The Evolution of the RDA Work to the Share-VDE Opus and BIBFRAME Hub -- PH-remix prototype A non relational approach for exploring AI-generated content in audiovisual archives -- The SSH Data Citation Service, a tool to explore and collect citation metadata -- B!SON: A Tool for Open Access Journal Recommendation -- Visual Web Archive Quality Assessment -- The Knowledge Trust: A Proposal for a Blockchain Consortium for Digital Archives -- Enabling Portability and Reusability of Open Science Infrastructures -- Simulating User Querying Behavior using Embedding Space Alignment -- A Closer Look into Collaborative Publishing at Software-Engineering Conferences -- Design and evaluation of a mobile application for an Italian UNESCO site: Padova Urbs picta -- Ontology-based metadata integration for Oral History Interviews -- Making FAIR Practices Accessible and Attractive -- Structured references from PDF articles: assessing the tools for bibliographic reference extraction and parsing -- On Dimensions of Plausibility for Narrative Information Access to Digital Libraries -- Early Experiments on Automatic Annotation of Portuguese Medieval Texts -- Creating Structure in Web Archives With Collections: Dierent Concepts From Web Archivists -- Weighted Altmetric Scores to Facilitate Literature Analyses -- Accelerating Innovation Papers -- Exploring LSTMs for Simulating Search Sessions in Digital Libraries -- Got 404s? Crawling and Analyzing an Institutions Web Domain -- Automatic Knowledge Extraction from a Digital Library and Collaborative Validation -- Holistic Graph-based Representation and AI for Digital Library Management -- Optimizing the digitization workflow of heritage institutions to increase quality of digitized texts -- Mapping STI ecosystems via Open Data: overcoming the limitations of conflicting taxonomies. A case study for Climate Change Research in Denmark? -- BetterPR: A Dataset for Estimating the Constructiveness of Peer Review Comments -- BookSampo Fiction Literature Knowledge Graph Revisited: Building a Faceted Search Interface with Seamlessly Integrated Data-analytic Tools -- Solutions for data sharing and storage: a comparative analysis of data repositories -- LOD that picture: leveraging Linked Open Data to enhance navigation of the photographic archive of the Teatro Comunale of Bologna -- MedSeer: A Medical Controversial Information Retrieval System Based On Credible Sources -- Referency: Harmonizing citations in transdisciplinary scholarly literature -- A Study of the Grammacographical Textual Genre Across Time -- A Methodology for the Management of Contact Languages Data. The Case Study of the Jews of Corfu -- SurvAnnT: Facilitating Community-led Scientific Surveys and Annotations.
Keywords: Application software; Coding theory; Information theory; Software engineering; Natural language processing (Computer science).; Image processing; Computer and Information Systems Applications; Coding and Information Theory; Software Engineering; Natural Language Processing (NLP).; Image Processing